Iot Based Health Monitoring System for Persons with Intellectual Disabilities - Narendar Singh, D.; Sudhir Kr. Sharma, Prof; Farukh Hashmi, Dr. (International Journal of Engineering and Technology, 2026)
IoT (Internet of Things) is utilized as a part of a great deal of uses. A portion of the uses of Internet of Things are savvy stopping, shrewd home, brilliant city, keen condition, mechanical spots, horticulture fields and wellbeing observing procedure. One such application is in medicinal services to screen the patient wellbeing status by means of Internet of Things makes therapeutic gear more effective by permitting ongoing checking of patient wellbeing, in which sensor get information of patient's and decreases the human blunder. The Internet of Things in the therapeutic field draws out the answer for compelling continuous checking of rationally impaired individual at diminished cost and furthermore lessens the exchange off between tolerant result and infection administration. So far we have seen the wellbeing observing framework which gathers data of fundamental parameters, for example, heart beat, temperature, circulatory strain and development parameters. In this paper we examine about checking patient's mind flags and recognizing the status of the patient progressively. To gather the information of cerebrum signals, we are utilizing Neurosky Mindwave Mobile Headset which deals with the EEG innovation. It demonstrates the yield result in waveform design. In this paper the fundamental point is to give legitimate and productive therapeutic administrations to patients by gathering information data of cerebrum and other body parameters through sensors which would incorporate patient's heart rate, body temperature and EEG (Electro Encephalograph). In the event that the gathered information is underneath than the normal esteem it sends a crisis alarm to patient's specialist with his present status and full restorative data. Besides, the framework spares the patient's customized estimations to a cloud-based information store progressively.
Keywords: IOT; EEG; CloudStorage; Raspbean; VNC server.